First record and five new species of Xylographellini (Coleoptera: Ciidae) from China, with online DNA barcode library of the family - Lopes-Andrade, Cristiano; Grebennikov, Vasily V. (Zootaxa, 2015)
We report the first record of the beetle tribe Xylographellini (Ciidae) from the continental Palaearctic Region, represented by five new species discovered in Yunnan and Sichuan provinces, China: Scolytocis danae sp. nov., Syncosmetus euryale sp. nov., Sync. medusa sp. nov., Sync. perseus sp. nov. and Sync. stheno sp. nov. Illustrations and identification keys are provided for these new species, and in order to facilitate further research of Ciidae we present an open-access DNA barcode library (dx.doi.org/10.5883/DS-SYNCOSM) containing 114 records (of 44 species in 14 genera), 15 of which belong to the newly described species. A phylogenetic analysis based on the barcode fragment of the cytochrome oxidase I gene did not recover much tree structure within Ciidae, however both Xylographus Mellié and Syncosmetus Sharp were recovered as clades, with a single Scolytocis Blair being the sister to the latter.